Introduction to public health : promises and practices - Goldsteen, Raymond L.; Goldsteen, Karen; Dwelle, Terry L. (Springer Publishing Company, 2025)
"This book describes the public health system in broad strokes in order to focus the reader on basic public health goals, principles, structures, and practices. The context in which public health is practiced today has changed considerably since its historic roots in the Industrial Revolution of the 18th and 19th centuries. As a result, public health practices are changed and changing still. However, the overarching goal of public health systems remains the same-to ensure through collective action a healthful environment for all. The 21st century offers incredible challenges to public health. The disparity in access to healthy environments is widening, and the threats to health concern the foundations of health, including adequate and nutritious food, clean and sufficient water, and shelter. Moreover, these are global problems that touch every country to some extent and threaten to affect all countries within our lifetimes. This fact was made particularly clear by the COVID-19 pandemic"--